Pharmacokinetics of clopidogrel after administration of a high loading dose - Taubert, Dirk; Kastrati, Adnan; Harlfinger, Steffi; Gorchakova, Olga; Lazar, Andreas; von Beckerath, Nicolas; Schömig, Albert; Schömig, Edgar (Thrombosis and Haemostasis, 2004)
The adenosine diphosphate (ADP) receptor P2Y12 blocking agent clopidogrel is clinically proven to be efficient in preventing thrombotic events. However, its therapeutic value is limited by an, as yet poorly explained, interindividual heterogeneity in platelet inhibition. To evaluate possible pharmacokinetic determinants of this response variability, we developed a sensitive and specific liquid chromatography tandem mass spectrometry (LC-MS/MS) assay for quantification of unmodified inactive clopidogrel, its inactive carboxyl metabolite, and its active thiol metabolite in plasma. Analyte concentrations and platelet aggregation were assessed in ten healthy volunteers receiving an oral load of 600 mg clopidogrel. Subjects showed marked inter-individual differences in maximal platelet inhibition and in plasma pharmacokinetics. Univariate regression revealed linear correlations between maximal antiplatelet effect and peak plasma concentrations (cmax) of unchanged clopidogrel (r=0.76; p=0.01), of the carboxyl metabolite (r=0.70; p=0.03), and of the thiol metabolite (r=0.73; p=0.02), as well as linear correlations between cmax values of clopidogrel and its metabolites. This indicates that the response variability is predominantly caused by individual differences in clopidogrel absorption and that other factors, such as ADP receptor reactivity or differences in bioactivation of clopidogrel, do not play a major role.
Keywords: Clopidogrel; pharmacokinetics; platelet inhibition; response variability